Pure-phase VO2 self-supporting aerogels and their synthesis methods

CN122916211APending Publication Date: 2026-10-16SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611304746.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]VO2气凝胶的制备通常依赖多步工艺,例如先合成VO2粉体再复合载体,或采用模板法构建多孔结构,前述方法存在流程复杂、周期长、易引入杂质、结晶度和化学计量比难以控制等问题

Benefits of technology

[0023] Compared with existing technologies, this invention does not require the introduction of an inert framework or pore-forming agents and binders in advance, thus avoiding interference from foreign impurities on phase change performance, significantly simplifying the process flow, and realizing the simple preparation of high-purity, self-supporting VO2 aerogels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916211A_ABST
    Figure CN122916211A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of aerogel preparation, and discloses pure-phase VO2 self-supporting aerogel and a synthesis method thereof, which comprises the following steps: S1, introducing layered V2CT X MXene is prepared to form a suspension; S2, the suspension is subjected to freeze drying to obtain a skeleton material; and S3, the skeleton material is subjected to heat treatment in an oxygen-containing atmosphere to obtain pure-phase VO2 aerogel. The application does not need to previously introduce an inert skeleton or introduce a pore-forming agent and a binder, avoids interference of external impurities on phase change performance, significantly simplifies a process flow, and realizes simple preparation of high-purity self-supporting VO2 aerogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aerogel preparation technology, and more specifically, to pure-phase VO2 self-supporting aerogels and their synthesis methods. Background Technology

[0002] The preparation of VO2 aerogels typically relies on multi-step processes, such as first synthesizing VO2 powder and then composite it with a carrier, or using a template method to construct a porous structure. These methods suffer from problems such as complex processes, long cycles, easy introduction of impurities, and difficulty in controlling crystallinity and stoichiometry. Furthermore, VO2 prepared by traditional methods... Aerogels often require an external supporting substrate, making it difficult to obtain a self-supporting, high-purity three-dimensional continuous network structure, thus limiting their application in gradient phase transitions, reconfigurable terahertz modulation, and other fields. Summary of the Invention

[0003] Currently, typical non-pure phase VO2 aerogel processes include the following three types: (1) Carbon skeleton loading method: VO2 powder is loaded onto a carbon-based aerogel derived from acetyl chitosan as a skeleton, and then freeze-dried and calcined in a nitrogen atmosphere to obtain the material, which is a VO2 / carbon composite aerogel. The carbon skeleton is permanently retained as a non-VO2 component.

[0004] (2) Silica composite framework method: using industrial water glass as silicon source and vanadium pentoxide as vanadium source, VO2-SiO2 composite aerogel is synthesized in situ through solvothermal reaction and supercritical drying. The SiO2 framework runs through the entire porous network, and VO2 is loaded in the form of nanorod-shaped crystals.

[0005] (3) Polymer fiber composite matrix method: After surface modification of VO2 powder, it is composited with carboxylated carbon nanotubes, then mixed with aramid nanofiber (ANF) dispersion, and freeze-dried to obtain CNTs / VO2 / ANF composite aerogel. The polymer fiber and carbon nanotubes constitute the supporting matrix.

[0006] The aforementioned methods all rely on external framework materials (carbon, SiO2, polymer fibers, etc.) to support the VO2 component, resulting in composite aerogels rather than pure-phase VO2 self-supporting structures. These aerogels, which depend on external framework materials, have the following drawbacks: Firstly, since it is an exogenous framework material, impurities will interfere with the intrinsic phase transition behavior of VO2, thereby reducing the infrared / terahertz modulation depth and introducing additional scattering and absorption losses.

[0007] Secondly, the foreign skeleton occupies a large space, the actual VO2 content is low, and it is easy to be unevenly distributed, resulting in discontinuous phase transition function and difficulty in achieving precise three-dimensional gradient phase transition control.

[0008] Third, it is necessary to prepare or introduce a framework before VO2 composite, which involves many steps and a long cycle. Furthermore, the interfacial bonding between the framework and VO2 is weak, and it is prone to peeling and pulverization after long-term use.

[0009] Based on the aforementioned shortcomings, the applicant conducted an in-depth analysis and found that the underlying reason is that VO2 crystallization usually requires high-temperature treatment, while conventional aerogel skeletons are prone to shrinkage, collapse or side reactions at high temperatures. Therefore, it is necessary to adopt the strategy of pre-preparing an inert skeleton and then recombining VO2, which forces the introduction of impurities.

[0010] Therefore, it is necessary to overcome the aforementioned technical problem of being forced to introduce impurities due to the pre-prepared inert framework. Furthermore, This invention provides a method for synthesizing pure-phase VO2 self-supporting aerogels, which directly yields pure-phase VO2 aerogels with a three-dimensional continuous porous structure without introducing any external framework materials or templates. Specifically, it includes the following steps: S1 will use layered V2CT X MXene is prepared to form a suspension; Specifically, this refers to layered V2CT. X MXene is dispersed in a polar solvent to prepare a suspension with a concentration of 1-50 mg / mL. Specifically, the concentration can be 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 mg / mL. More specifically, it can be any range of the above values, such as 5-50 mg / mL, 10-50 mg / mL, 15-50 mg / mL, ..., 20-50 mg / mL, etc. Even more preferably, the concentration is 10-20 mg / mL; even more preferably, it is 15 mg / mL.

[0011] As mentioned above, the polar solvent includes at least one of water and ethanol.

[0012] In the aforementioned, layered V2CT X The average particle size of MXene is 5~10μm, and the number of layers is 5~15, which can be further selected as 3~8 layers.

[0013] via V2CT X MXene, as the sole vanadium source and structural precursor, leverages its excellent dispersibility and lamellar morphology to lay the foundation for subsequent construction of a self-supporting network. V2CT was selected. X MXene is due to its superior properties compared to other vanadium-based MXenes, such as V4C3T. X MXene has a more layered structure, and its etching process is more efficient than V2CT. X MXene is more difficult, V4C3T X MXene itself is better than V2CTX MXene has more V atom valence states, and the average V atom valence states are generally higher than those of V2CT. X MXene has a low valence state, so its oxidation requires more oxygen and the oxidation window is more difficult to control, easily yielding various heterogeneous V oxides. Based on this, we employ V2CT. X MXene, the self-limiting oxidation process utilizing it, actually uses water as an oxygen source, water and V2CT X The MXene reaction actually produces CO / CO2 reducing gases, compared to V4C3T. X MXene uses an oxygen-rich atmosphere for oxidation, while water provides a milder oxidation condition and allows for more thorough removal of V2CT through the water-gas reaction. X The C element in MXene more fully utilizes V2CT X MXene is converted to VO2.

[0014] S2 involves freeze-drying the suspension to obtain the skeleton material; Through freeze-drying, ice crystals sublimate to form interconnected channels, V2CT X Nanosheets self-assemble and overlap along the pore walls, forming a continuous three-dimensional network framework that requires no binder or external substrate. This framework exhibits high porosity, large specific surface area, and good mechanical integrity.

[0015] As described above, the suspension is injected into a mold for freeze-drying. There are no specific restrictions on the shape of the mold; for example, a cylindrical mold (2 cm in diameter and 1 cm in height) can be used. Freezing is performed using a freeze dryer.

[0016] In the aforementioned process, freeze-drying involves pre-freezing the suspension at -20 to -196°C for 2-24 hours, followed by freeze-drying for 24-72 hours to obtain the framework material (V2CT). X (Self-supporting aerogel). Preferably, it is pre-frozen at -30°C for 4 hours, and then freeze-dried for 48 hours. The resulting aerogel is a black block.

[0017] S3 The framework material was heat-treated in an oxygen-containing atmosphere to obtain pure phase VO2 aerogel; During heat treatment, V2CT X In the laminate, V(-II) and C undergo oxidation, with C escaping as CO2 and V being oxidized to V2. 4+In-situ crystallization generates pure-phase VO2 while fully inheriting the original porous aerogel structure. By controlling the heat treatment parameters, the grain size, crystallinity, and oxygen vacancy concentration of VO2 can be directly adjusted within the pure-phase system, thereby regulating the phase transition temperature, thermal hysteresis width, and modulation depth. For example, higher temperatures promote grain growth and reduce phase transition thermal hysteresis; lower temperatures yield nanocrystals, improving the response speed. Due to the absence of impurity phase interference, the adjustment effect is even more significant.

[0018] In the aforementioned, the obtained V2CT X The self-supporting aerogel is placed in an oxygen-containing atmosphere and heat-treated at a temperature of 500-800℃ for 1-6 hours. Specifically, the temperature can be 500, 550, 600, 650, 700, 750, or 800℃, or any range of these values, such as 550~800℃, 600~800℃, 650~800℃, 700~800℃, or 750~800℃. More preferably, the temperature is 600~700℃, and even more preferably, 650℃.

[0019] The oxygen-containing atmosphere includes at least one of air, oxygen, and an inert gas mixture; the volume ratio of oxygen in the mixture is 15-30%, and the inert gas includes at least one of argon and nitrogen. An air atmosphere is preferred.

[0020] In this invention, we use V2CT X As a precursor, it serves as both a vanadium source and a structural template. Utilizing its unique two-dimensional layered structure and chemical composition, it can form a stable self-supporting framework after freeze-drying and be directly converted into VO2 during oxidative heat treatment without the need for additional framework materials, thus avoiding the problem of introducing impurities.

[0021] In this invention, freeze-drying is the key to achieving a self-supporting porous network, endowing the material with high porosity and a three-dimensional interconnected structure, providing a structural basis for the subsequent in-situ conversion of VO2.

[0022] In this invention, in-situ oxidation transformation is achieved through heat treatment. Specifically, V2CT is transformed into a single step by completing the decarburization, oxidation, and crystallization process. X The framework is transformed into a pure-phase VO2 aerogel. By controlling the atmosphere and temperature parameters, VO2 with a strict stoichiometric ratio of V:O=1:2, no impurity phase, and high crystallinity can be obtained while maintaining the aerogel morphology.

[0023] Compared with existing technologies, this invention does not require the introduction of an inert framework or pore-forming agents and binders in advance, thus avoiding interference from foreign impurities on phase change performance, significantly simplifying the process flow, and realizing the simple preparation of high-purity, self-supporting VO2 aerogels.

[0024] Compared with existing technologies, this invention uses V2CT. X MXene, as the sole vanadium source and structural precursor, forms a self-supporting V2CT after freeze-drying. X Aerogel, and then V2CT through in-situ oxidative heat treatment. X The aerogel is completely converted to pure-phase VO2, during which carbon escapes as CO2, leaving no residual framework. Therefore, the resulting product is a pure-phase VO2 aerogel with a strict stoichiometric ratio of V:O = 1:2, free from impurities, maximizing its phase transition properties. In this invention, the entire aerogel framework is composed of VO2 itself, without any additional framework spacers, and the volume fraction of VO2 can reach 100% of the aerogel framework (excluding pores). Simultaneously, the in-situ conversion process preserves the original V2CT. X The interconnected structure of the framework, with VO2 grains continuously distributed in three dimensions along the pore walls, preserves a large air content in the V2CTx aerogel template, enabling good thermal insulation after the internal VO2 phase transition, which is beneficial for precise gradient phase transition control.

[0025] Compared with existing technologies, the process steps of this invention are simpler, and the overall process is greatly simplified. It requires no template agents, binders, or subsequent solvent replacement, significantly reducing raw material costs and labor and energy consumption. Due to the reduced number of steps, there are fewer process control variables, resulting in higher batch repeatability. The VO2 aerogel obtained by this invention is a complete self-supporting block with sufficient mechanical strength (derived from the three-dimensional network of interconnected VO2 nanosheets). It can be directly cut, clamped, or transferred without an additional substrate, greatly facilitating subsequent laser direct writing, gradient heating control, and cross-band stealth metasurface integration. Attached Figure Description

[0026] Figure 1 V2CT in Example 1 X A photograph of a self-supporting aerogel; Figure 2 This is a photograph of the pure-phase VO2 aerogel in Example 1; Figure 3 The image shows the XRD pattern of the pure-phase VO2 aerogel in Example 1. Figure 4 Here is a SEM image of the pure-phase VO2 aerogel in Example 1; Figure 5 , Figure 6 This is an EDS result image of the pure-phase VO2 aerogel in Example 1; Figure 7 The image shows the DSC diagram of the pure-phase VO2 aerogel in Example 1. Figure 8 This is an infrared transmission result of the pure-phase VO2 aerogel in Example 1; Figure 9The graph shows the temperature resistance test results of the pure phase VO2 aerogel in Example 1; Figure 10 This is a photograph of the aerogel in Example 4 that was not pre-frozen; Figure 11 The image shows the infrared modulation results of the VO2 aerogel in Comparative Example 1. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0028] Example 1 This embodiment provides a method for synthesizing pure-phase VO2 self-supporting aerogel, including the following steps: Step 1: V2CT X MXene material (average particle size 5-10 μm, number of layers 3-8) was dispersed in deionized water and ultrasonically dispersed for 30 minutes to prepare a uniform dispersion with a concentration of 15 mg / mL.

[0029] Step 2: Inject the above dispersion into a cylindrical mold (2 cm in diameter, 1 cm in height) and place it in a freeze dryer. Pre-freeze at -30°C for 4 hours, then freeze-dry under a vacuum of <10 Pa for 48 hours to obtain V2CT. X Self-supporting aerogel. This aerogel is a dark brown-gold block (see...). Figure 1 (), density approximately 0.03 g / cm³ 3 The porosity is approximately 95%.

[0030] Step 3: V2CT X The self-supporting aerogel was placed in a tube furnace and heated to 650°C at a heating rate of 5°C / min under air atmosphere, held at that temperature for 2.5 hours, and then allowed to cool naturally to room temperature. During this process, V2CT... X Oxidative decomposition occurs, with carbon escaping as CO2 and v being oxidized to VO2, which then crystallizes in situ to form a pure-phase VO2 aerogel. The resulting product is a deep blue-black self-supporting mass (see...). Figure 2 It retains its original macroscopic shape and microscopic porous structure. Its density is approximately 0.024 g / cm³. 3 The porosity is approximately 99.4%.

[0031] Characterized by X-ray diffraction (XRD) (see Figure 3 The product only shows characteristic diffraction peaks of VO2 (M phase), without impurity peaks such as V2O5 and V2O7, and has a crystallinity of >95%.

[0032] Scanning electron microscope (SEM) (see Figure 4 The results show that VO2 nanosheets are interconnected to form a three-dimensional network with a layer thickness of approximately 50-200 nm.

[0033] Energy dispersive spectroscopy (EDS) (see Figure 5 , Figure 6 The V:O atomic ratio is given as 1:2.02, which is close to the ideal stoichiometric ratio.

[0034] Differential scanning calorimetry (DSC) (see...) Figure 7 The display shows that the phase transition start temperature is 68℃ and the thermal hysteresis width is about 13℃.

[0035] Infrared transmission test (wavelength 8-12μm) (see) Figure 8 The results showed that after heating to 80℃, the transmittance decreased by approximately 20.2%, comparable to the high-performance VO2 reported in the literature. The aforementioned infrared transmittance test used the KBr powder pressing method; however, in this technology, the aerogel is made using V2CT. X To construct the template, it is necessary to know the phase transition properties of VO2 in the prepared aerogel. Therefore, the aerogel is crushed into powder and then subjected to KBr pellet testing. Firstly, due to KBr dilution and powder particle scattering effects, the transmittance modulation amplitude is usually much smaller than the measured values ​​of the film's reflectance / emissivity. However, as... Figure 8 As shown, the VO2 powder prepared by this invention still achieves an infrared transmittance reduction of approximately 20.2% after heating to 80°C. Under stringent testing conditions excluding substrate interference and signal attenuation, this high reduction fully demonstrates that the VO2 powder of this invention possesses extremely high phase transition efficiency and excellent crystal quality, and its intrinsic infrared switching performance is comparable to that of high-performance VO2 prepared using optimal processes as reported in the literature. Figure 9 The figure shows the curve of the prepared pure-phase VO2 aerogel changing with temperature (the result of the temperature resistance test). Figure 9 It can be seen that its sheet resistance is on the order of three, while the sheet resistance of most VO2 varies on the order of two, fully demonstrating the superiority of its phase transition performance.

[0036] Example 2 Follow the same steps as in Example 1, only changing V2CT in step 1. X The concentrations of the dispersions were prepared at 5 mg / mL and 20 mg / mL, respectively.

[0037] At a concentration of 5 mg / mL, the resulting aerogel exhibited higher porosity (approximately 98%) and a more porous framework. The density of the heat-treated VO2 aerogel was approximately 0.01 g / cm³. 3The infrared modulation depth is approximately 15%. This material is suitable for integrated thermal insulation and stealth applications where lower density is required.

[0038] At a concentration of 20 mg / mL, the aerogel porosity is approximately 92%, resulting in a denser framework. After heat treatment, the density of the VO2 aerogel is approximately 0.08 g / cm³. 3 With an infrared modulation depth of up to 28%, it is suitable for terahertz control devices that require strong phase transition response.

[0039] The products at both concentrations were pure phase VO2 with no impurity peaks, indicating that the process has a wide range of concentration adaptability.

[0040] Example 3 The same steps as in Example 1 were followed, except that the heat treatment temperature in step 3 was changed to 600°C and 700°C respectively, and the holding time was 2.5 hours for both.

[0041] Treatment at 600℃: The product crystallinity is slightly lower (approximately 85%), the VO2 grain size is approximately 30-50 nm, the phase transition temperature increases to 72℃, and the thermal hysteresis width is approximately 12℃. The infrared modulation depth is approximately 18%.

[0042] Treatment at 700℃: VO2 grains grow to 100-300 nm, crystallinity >98%, phase transition temperature decreases to 62℃, thermal hysteresis width is about 5℃, and infrared modulation depth is about 25%. Trace amounts of V2O5 impurities appear in some samples (XRD peak intensity <3%).

[0043] Example 4 Following the same steps as in Example 1, but with a change in the freeze-drying process: The pre-freezing temperature was changed to -196℃, and liquid nitrogen was used for rapid freezing. Specifically, a PTFE mold was placed in a metal tray, then the V2CTx dispersion was added to the PTFE mold. Liquid nitrogen was then poured into the metal tray, and the tray was covered with foam board. Within 3-5 minutes, the V2CTx dispersion in the mold was completely frozen and solidified. It was then transferred to the cold trap of a freeze dryer, shortening the freeze-drying time to 24 hours. The resulting V2CT... X The aerogel has smaller pore size (average pore size 2-5 μm) and a more uniform structure. The final VO2 aerogel has a higher specific surface area, an infrared modulation depth of 23%, and a phase transition thermal hysteresis width of only 6℃.

[0044] If freeze-drying is performed directly without pre-freezing (placing the mold in a cold trap), ice crystal growth becomes uncontrolled, resulting in an uneven aerogel structure, localized collapse, and ultimately, cracking of the VO2 aerogel, leading to a decline in performance. The results are as follows: Figure 10 As shown.

[0045] Example 5 Following the same steps as in Example 1, the air atmosphere in step 3 was replaced with an oxygen / argon mixture with an oxygen volume fraction of 20% (the remainder being argon). The results were essentially the same as those under an air atmosphere, except for a slightly higher infrared modulation depth (approximately 23.5%), but the cost increased. Using a pure oxygen atmosphere results in intense exothermic activity, and the aerogel framework is prone to localized overheating and pulverization; therefore, this approach is not recommended.

[0046] Comparative Example 1 The comparative example provides a conventional method for preparing VO2 aerogels, as follows: Step 1: Disperse cellulose nanofibers (CNF, diameter 5-20 nm) in deionized water and sonicate for 20 min to prepare a suspension of 10 mg / mL. Pour the suspension into a cylindrical mold (diameter 2 cm, height 1 cm), pre-freeze at -28℃ for 5 h, and freeze-dry under vacuum <10 Pa for 48 h to obtain a white CNF aerogel framework (density approximately 0.02 g / cm³).

[0047] Step 2: Immerse the CNF aerogel in a 0.15 mol / L vanadium oxysulfate (VOSO4) aqueous solution under vacuum for 30 min. After removal, transfer to a hydrothermal reactor and react at 180℃ for 16 h. Then anneal at 550℃ for 2 h under air atmosphere with a heating rate of 3℃ / min to obtain the VO2 / CNF composite aerogel. The product is a gray-black block with a volume shrinkage of approximately 35%, a density of approximately 0.045 g / cm³, and a porosity of approximately 90%.

[0048] Step 3: Infrared emissivity testing of the product (temperature variation 25–100℃) showed a modulation amplitude of only 0.12 (see...). Figure 11 The value was much lower than the 0.22 of the pure phase VO2 aerogel in the examples, indicating that residual cellulose template and uneven VO2 distribution severely weakened the infrared modulation performance.

Claims

1. A method for synthesizing a pure-phase VO2 self-supporting aerogel, characterized in that, Includes the following steps: S1 will use layered V2CT X MXene is prepared to form a suspension; S2 involves freeze-drying the suspension to obtain the skeleton material; S3 The framework material was heat-treated in an oxygen-containing atmosphere to obtain pure phase VO2 aerogel.

2. The synthesis method according to claim 1, characterized in that, In S1, the concentration of the suspension is 1~50 mg / mL, and / or the solvent in the suspension includes at least one of water and ethanol.

3. The synthesis method according to claim 2, characterized in that, In S1, the concentration of the suspension is 10~20 mg / mL.

4. The synthesis method according to claim 1, characterized in that, In S1, layered V2CT X The average particle size of MXene is 5~10μm, and the number of layers is 5~15.

5. The synthesis method according to claim 1, characterized in that, In S2, the suspension is first pre-frozen at -20~-196℃ for 2-24 hours, and then freeze-dried for 24-72 hours.

6. The synthesis method according to claim 5, characterized in that, In S2, the suspension is first pre-frozen at -30°C for 4 hours, and then freeze-dried for 48 hours.

7. The synthesis method according to any one of claims 1 to 6, characterized in that, In S3, heat treatment: 500-800℃ for 1-6 hours; and / or, the oxygen-containing atmosphere includes at least one of air, oxygen and an inert gas mixture.

8. The synthesis method according to claim 7, characterized in that, Heat treatment: 600~700℃.

9. The synthesis method according to claim 7, characterized in that, The oxygen-containing atmosphere is air.

10. A pure-phase VO2 self-supporting aerogel obtained by the synthesis method according to any one of claims 1 to 9.